Android-Based 'Tire-Math' Application Development: Integration of Business Mathematics in Receivables Management in MSMEs Tire Recycling to Support SDG 12 - Qurrotu A'yunin; Rani Darmayanti (Universitas Muhammadiyah Malang, 2026)
The issue of waste tires demands green entrepreneurial solutions to support the Sustainable Development Goals (SDG) 12 targets. However, MSMEs recycling tires in Surengrono face serious receivables management obstacles due to manual recording systems that have not implemented formal business mathematical concepts. This research aims to develop an Android-based